Development of the ProProfs platform as an E-Quiz for Arabic Language Learning in Early Childhood Education - Sarip, Mohamad; Linty, Mathieu; Kurniadi, Pahar; Erliana, Leni; Xavier, Embrechts (Journal International of Lingua and Technology, 2024)
The development of technology has a huge impact on the education system, there are many free platforms that provide applications to create learning media. One of them is the ProProfs platform, this platform can be used to create online Quiz. The purpose of the research is to utilize and develop the ProProfs platform as Arabic learning media for online Quiz at the Early Childhood Education level. This research method uses the Development Method (Research and Development) using the ASSURE model whose steps are as: (1) analyze student characteristics; (2) determine learning objectives; (3) choose methods, media, and learning strategies; (4) use learning materials; (5) conduct evaluation and revision. The results of this study explain that the ProProfs platform can be used to improve Early Childhood achievement with evidence that these children have memorized more than 100 Arabic vocabulary. The conclusion of the research is to explain that the ProProfs platform can help teachers in making E-Quiz, so that students are happy and interested in learning Arabic. The limitation of the study is that researchers only conducted research in Early Childhood education, which incidentally these children do not understand technology and need supervision from teachers, for that the researcher hopes that future researchers can conduct research with the same platform but developed at a higher level.